MiR-137 and miR-34a directly target Snail and inhibit EMT, invasion and sphere-forming ability of ovarian cancer cells. Issue 1 (December 2016) - Dong, Peixin; Xiong, Ying; Watari, Hidemichi; Hanley, Sharon; Konno, Yosuke; Ihira, Kei; Yamada, Takahiro; Kudo, Masataka; Yue, Junming; Sakuragi, Noriaki
Abstract Background In ovarian cancer (OC) cells, Snail was reported to induce the epithelial-to-mesenchymal transition (EMT), which is a critical step in OC metastasis. At present little is known about controlling Snail expression in OC cells by using specific microRNAs (miRNAs). Methods We first used a computational target prediction analysis to identify 6 candidate miRNAs that bind to the 3′-untranslated region (3′-UTR) region of theSnail mRNA. Among these miRNAs, two miRNAs (miR-137 and miR-34a) with a potential to regulate Snail were validated by quantitative real-time PCR, Western blot analysis, andSnail 3′-UTR reporter assays. We assessed the effects of miR-137 and miR-34a on EMT, invasion and sphere formation in OC cells. We also evaluated the expression of miR-137 and miR-34a in OC tissues and adjacent normal tissues and analyzed the relationship between their expression and patient survival. Results We report that OC tissues possess significantly decreased levels of miR-137 and miR-34a and increased expression ofSnail when compared to their adjacent normal tissues, and lower miR-137 and miR-34a expression correlates with worse patient survival. Using luciferase constructs containing the 3′-UTR region ofSnail mRNA combined with miRNA overexpression and mutagenesis, we identified miR-137 and miR-34a as direct suppressors ofSnail in OC cells. The introduction of miR-137 and miR-34a resulted in the suppression of Snail at both the transcript and protein levels, and effectively suppressed the EMT phenotype and sphere formation of OC cells. However, the inhibition of miR-137 and miR-34a with antisense oligonucleotides promoted EMT and OC cell invasion. Moreover, ectopic expression of Snail significantly reversed the inhibitory effects of miR-137 and miR-34a on OC cell invasion and sphere formation. Conclusions These findings suggest that both miR-137 and miR-34a act as Snail suppressors to negatively regulate EMT, invasive and sphere-forming properties of OC cells.